Knockdown of m6A Reader IGF2BP3 Inhibited Hypoxia-Induced Cell Migration and Angiogenesis by Regulating Hypoxia Inducible Factor-1α in Stomach Cancer - Jiang, Libin; Li, Yingxia; He, Yixin; Wei, Dapeng; Yan, Lvyin; Wen, Hongtao (Frontiers in Oncology, 2021)
Hypoxia is a common feature of solid tumors including stomach cancer (SC) and is closely associated with cancer malignant progression. N6-methyladenosine (m6A), a common modification on RNA, is involved in the regulation of RNA fate and hypoxic responses in cancers. However, the interaction between m6A reader insulin-like growth factor-II mRNA-binding protein 3 (IGF2BP3) and SC hypoxic microenvironment is poorly defined. In the present study, expression levels of IGF2BP3 and hypoxia inducible factor-1α (HIF1A) were examined by bioinformatics analysis and RT-qPCR and western blot assays. Cell migratory ability was assessed through Transwell and wound healing assays. The angiogenic potential was evaluated by VEGF secretion, tube formation, and chick embryo chorioallantoic membrane (CAM) assays. The interaction between IGF2BP3 and HIF1A was explored using bioinformatics analysis and RIP and luciferase reporter assays. The results showed that IGF2BP3 and HIF1A were highly expressed in SC tissues and hypoxia-treated SC cells. IGF2BP3 knockdown inhibited hypoxia-induced cell migration and angiogenesis in SC. IGF2BP3 positively regulated HIF1A expression by directly binding to a specific m6A site in the coding region of HIF1A mRNA in SC cells. HIF1A overexpression abrogated the effects of IGF2BP3 knockdown on hypoxia-induced cell migration and angiogenesis in SC. In conclusion, IGF2BP3 knockdown inhibited hypoxia-induced cell migration and angiogenesis by down-regulating HIF1A in SC.